1982
DOI: 10.1159/000233149
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Inhibition of Rapid Expulsion of <i>Trichinella spiralis </i>in Rats

Abstract: A variety of inhibitors was examined for their ability to interfere with the expression of rapid expulsion (RE) of challenge Trichinella spiralis infections in rats. Inhibitors of immediate hypersensitivity, prostaglandin release, peristalsis, or complement function, did not impair RE when administered to immune rats. Induction of intestinal anaphylaxis against T. spiralis or ovalbumin by passive serum transfer to intestinally primed rats (prior infection with Heligmosomoides polygyrus) or administration of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Previous studies showed a correlation between T. spiralis expulsion and mucosal mast cell degranulation, but a specific mediator or causal relationship was not identified (2)(3)(4)45). Rats maintain a resident population of mucosal mast cells in the lamina propria of the small intestine under homeostatic conditions (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed a correlation between T. spiralis expulsion and mucosal mast cell degranulation, but a specific mediator or causal relationship was not identified (2)(3)(4)45). Rats maintain a resident population of mucosal mast cells in the lamina propria of the small intestine under homeostatic conditions (46).…”
Section: Discussionmentioning
confidence: 99%
“…Support for the conclusion that mast cells are not pivotal in rapid expulsion was provided by studies using pharmacological agents that block histamine, serotonin, PGs, and intestinal motility (45). Treatment of infected adult rats with inhibitors of various mast cell effectors did not prevent rapid expulsion.…”
Section: Discussionmentioning
confidence: 99%
“…The immune system will certainly affect the activity of intestinal smooth muscle (Coulson, 1957). Castro et al (1976) have shown gut transit times to be decreased in Trichinella spiralis infected rats although inhibitors of intestinal motility did not prevent the characteristic rapid expulsion of these parasites from infected animals (Bell et al, 1982). Gut lymphoid tissue may also affect the functioning of epithelial cells (Castro, 1982).…”
Section: Responses To Anti-rat Igementioning
confidence: 99%
“…Pharmacological approaches have been employed in studies on rejection of T. spiralis [7,8,11]. In our test model the rapid onset of immune-mediated worm rejection allows us to use a single dose of drugs to mimic or prevent this process, obviating problems as sociated with the chronic administration of agents.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, rapid rejection can be partially transferred with im mune serum containing homocytotropic antibodies [10]. The major counterarguments against involve ment of anaphylaxis in worm rejection are that rapid rejection is not transferred by immune serum in some cases [11], that the role of homocytotropic antibodies in the process is ambiguous [12], and that drugs that inhibit the synthesis of mediators of anaphylaxis or antagonize their actions do not prevent worm rejec tion [11]. Because no quantitative measurements of in testinal immune responsiveness and/or of the effi cacy of drug on intestinal function were made in those studies yielding generally negative results, the conclu sions that can be drawn are limited.…”
Section: Introductionmentioning
confidence: 99%